SISTEM PENDUKUNG KEPUTUSAN SELEKSI CALON PENERIMA BEASISWA DI SEKOLAH TINGGI PENDIDIKAN ISLAM BINA INSAN MULIA YOGYAKARTA MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Yuli Praptomo PHS; Edi Sastrawijoyo (LPPM STMIK El Rahma Yogyakarta, 2020)
Bina Insan Mulia Yogyakarta College of Islamic Education offers a scholarship program for underprivileged and outstanding students. To determine the prospective scholarship recipients, the Islamic Education College of Bina Insan Mulia Yogyakarta still uses the manual method by comparing the criteria data one by one that must be adjusted to the predetermined criteria, this causes the selection process to experience difficulties and data errors due to the number of registrants many. This research aims to build a Scholarship Recipient Selection Decision Support System by applying the Simple Additive Weighting (SAW) method in it. The research method used is the study of literature which aims to study and understand the basic theories of decision support systems and the theory of Simple Additive Weighting (SAW). To find out the problem under study is the interview method, to find out information data relating to the problem under study is a method of collecting data and to study documents related to the object of research is the method of documentation. The results of testing the performance of the Decision Support System application using the Simple Additive Weighting (SAW) method stated that this system is able to provide a ranking of scholarship recipients' recommendations in accordance with the criteria used. The conclusion of this study is that this system was built to help the Islamic Education College of Bina Insan Mulia Yogyakarta to select prospective scholarship recipients. The method applied in this system is able to provide a solution to the problem of selection of prospective scholarship recipients with a ranking model that matches the applicable criteria and the weights of those criteria.